Strong yellow emission of ZnO hollow nanospheres fabricated using polystyrene spheres as templates - Zang, Zhigang; Wen, Mengqing; Chen, Weiwei; Zeng, Yangfu; Zu, Zhiqiang; Zeng, Xiaofeng; Tang, Xiaosheng (Materials & design, 2015)
ZnO hollow nanospheres were fabricated using polystyrene (PS) microspheres as templates were demonstrated in this paper. The structures and morphologies of obtained products were characterized by XRD, FESEM and TEM. The results revealed that ZnO hollow nanospheres possess a hexagonal wurtzite structure with a diameter around 450–500nm. Ultraviolet–visible (UV–vis) analysis showed that ZnO hollow nanospheres had high absorption in the ultraviolet region and low absorption in the visible region. Room temperature photoluminescence (PL) spectrum showed a weak UV emission at 380nm and a strong and broad yellow emission centered at 550nm. The formation mechanism of hollow structure was also investigated. [Display omitted] •ZnO hollow nanospheres synthesized by utilizing the PS microspheres as templates.•PS@ZnO core/shell structure influenced the morphology of ZnO hollow nanospheres.•ZnO hollow nanospheres with a strong yellow emission at the center of 550nm.•The intrinsic physical properties of ZnO hollow nanospheres were elucidated.